Spatial distribution model of Bornean Orangutan (Pongo pygmaeus wurmbii) habitat using logistic regression in Katingan watershed - Mustofa; Syartinilia; Hadi Susilo Arifin (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
Katingan watershed is a one of Bornean Orangutan (Pongo pygmaeus wrumbii) habitat that currently Critically Endangered status (IUCN 2016), and protected by Indonesian government regulations (P.106/2018), that included in Appendix 1 (CITES 2017). The condition of the Bornean Orangutan habitat is increasingly threatened by land cover changes. Management habitat is needed to protect the populations of Bornean Orangutan. The aim of this research was to develop the spatial distribution model of Bornean Orangutan habitat as a reference to habitat management. Habitat suitability model of Bornean Orangutan develop by logistic regression and based on five environmental variables covering elevation, distance from cultural sites, distance from roads, distance from settlements, and NDVI. The Hosmer-Lemeshow test showing feasibility value was 0.481 with Nagelker R2=0.866, and Kappa Accuracy 77%. The total habitat suitability of Bornean Orangutan in the Katingan watershed was 1,250,174.35 ha (64.11% of the Katingan watershed area). The main habitat of Bornean Orangutan was identify in the National Park (TN), Protection Forest (HL), and Nature Reserve/Nature Conservation Area (KSA/KPA) with area 395,178.30 ha (31.66% of the total habitat area). Isolated habitat identified in the north-eastern of the Katingan watershed. Habitat corridor can be reform with minimum width 500 meters in forest areas.